Fashion, fast or slow? Effects of binary and graded eco-labels on sustainable clothing purchases - Shane Timmons; Adam J. Shier; Olga Poluektova; Pete Lunn (The Economic and Social Research Institute (ESRI), 2024)
Excess clothing consumption severely harms the environment, through greenhouse gas emissions, resource degradation and water pollution. For consumers, however, the trade-off between this environmental impact and the convenience of "fast fashion" is hidden at the point of purchase. We present a pre-registered, experimental test of two clothing eco-labelling systems using a large, representative sample of consumers (N = 1,200). Participants used a simulated online clothing store, with some chosen at random to receive their selected items. They were randomised to see (i) a binary label, informed by existing policy, applied to the most sustainable products, (ii) a colour-coded, graded "eco-score" applied to all products, or (iii) no label. Compared to the control condition, participants exposed to binary label chose 10% more sustainable products. Eco-score participants, however, chose 20% more, and were twice as likely to exclusively buy the most sustainable products. There was no effect on the number of items purchased, implying a shift towards more sustainably produced clothing. Exploratory analyses revealed that the effects were driven by greater salience of the eco-score system and that effects were stronger among those most concerned about the environment. Those who saw the eco-labels reported the same level of shopping satisfaction and willingness to wear selected clothes as those in the control condition. Additional findings revealed a general underestimation of clothing production's environmental impact and strong support for implementing the eco-score both online and in-store. The results have implications for enabling informed consumer choice in the clothing market.
Keywords: 330; fast fashion; clothing; eco-label; experiment; consumer choice; environmental policy